The professional identity of mathematics teachers in Further Education - Dalby, D.M. (Adults Learning Mathematics, 2017)
Professional identities may be viewed as narrative constructions in social situations but personal experiences and beliefs are fundamental influences in their development. Within Further Education colleges in England, mathematics teachers are typically expected to fulfil multiple roles, teaching a wide range of curricula and age groups, and this brings additional complexity to their professional identities. In this study, questionnaires and interviews with mathematics teachers in three Further Education colleges are used to examine their roles and professional identities. The findings show how teachers’ personal experiences of mathematics, in formal education and the workplace, influence their beliefs and are linked to their narrative and working identities. These teachers enact complex and varied roles but develop a ‘leading professional identity’ that can be linked to significant critical events in the past.